Epidemiology of primary paediatric brain tumours at Johannesburg and Chris Hani Baragwanath hospitals from April 1995 to April 2005 - Nkusi, Agabe Emmy (My University, 2009)
Epidemiology of primary paediatric brain tumours has been studied extensively in developed countries of the west. Such studies are lacking in developing countries especially sub-Saharan Africa. This study seeks to establish the epidemiology of primary brain tumours seen among children that were treated at Chris Hani Baragwanath and Johannesburg Hospitals from April 1995 to April 2005. The records of 252 patients who presented with this condition during the study period were reviewed, for the following details: ● Demographic details such as age, gender and race ● Diagnosis and the date when it was made ● The follow-up period at the hospital(s)/clinic(s) ● The anatomical location of the tumours; supratentorial or infratentorial ● The treatment that was given which included mainly surgery for tumour removal or biopsy, radiotherapy, chemotherapy and others which included ventriculoperitoneal shunt, external ventricular drain insertion. ● The outcome of treatment included: - alive - dead - presumed alive - lost to follow-up It was found: ● That 225 patients had full demographic details of race, gender and age. ● That there was a slight male predominance among children with primary brain tumour. ● That the majority of children with brain tumours were black, followed by whites which is in keeping with the country’s demographics. ● The three most common tumours were astrocytomas, medulloblastomas and brainstem gliomas in the descending order of frequency. ● Medulloblastomas were the commonest tumours in the infratentorial region while craniopharyngiomas were commonest tumours in the supratentorial region. ● More children had infratentorial tumours ● Younger children were more likely to have infratentorial tumours. ● Majority of patients had surgery either for diagnosis or for diagnosis and treatment. ● Few patients were presumptively diagnosed clinically and by imaging modalities ● Combination therapy of surgery, chemotherapy and radiotherapy had the best survival outcome while chemotherapy as the only form of treatment had the worst outcome. ● The overall 5 year survival rate for all the study participants was much lower than that of their counterparts in the literature. ● Children who had craniopharyngiomas and astrocytomas had better survival. ● Mortality incidence was slightly higher for whites than blacks but that could have been skewed by a high number of blacks that was lost to follow-up. ● A higher infratentorial tumour prevalence than in the literature was noted. It was noted that racial prevalence of primary paediatric brain tumours follows population demographics. From the results of this study, there is a need for a better record keeping and improved patients follow-up. There is also a need for a larger epidemiological study in the two hospitals. There is need to establish a specialized paediatric unit which will help start a paediatric team comprising of a paediatric neurosurgeon, paediatric oncologist, paediatric intensivist and neuroradiologist with dedicated neuropaediatric ICU. Such a team given resources will improve survival outcome of children with brain tumours.
Keywords: brain tumours; children; epidemiology; Johannesburg hospital; Chris Hani Baragwanth hospital; 1995 - 2005